2010
DOI: 10.1002/nau.20927
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder in women: Does low‐count bacteriuria matter? A review

Abstract: Since the description of the overactive bladder (OAB) syndrome, which excludes infection, the precise definition of significant bacteriuria in these women is critical. The traditional definition of 'significant' bacteriuria is >10(5) colony-forming units/ml which was described 50 years ago by a renal physician whose primary interest was the prevention of pyelonephritis. Subsequent studies have shown this to be an insensitive threshold in women with acute lower urinary tract symptoms. Bacterial counts between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…This diagnostic threshold is important given the association between low-CFU bacteriuria count (<1,000 CFU per ml), urinary incontinence 50 and refractory LUTS. In those with a history of recurrent UTIs, requesting the results of the previous microscopy, culture and antibiotic sensitivity analyses can assist in confirming the diagnosis, determining the correct treatment based on sensitivities and determining whether the UTIs are recurrent or persistent 1 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…This diagnostic threshold is important given the association between low-CFU bacteriuria count (<1,000 CFU per ml), urinary incontinence 50 and refractory LUTS. In those with a history of recurrent UTIs, requesting the results of the previous microscopy, culture and antibiotic sensitivity analyses can assist in confirming the diagnosis, determining the correct treatment based on sensitivities and determining whether the UTIs are recurrent or persistent 1 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Several studies have suggested that this s-QBC cut-off may be inappropriate for some clinical conditions, and modified lower and higher cut-off values ranging from 10 3 to ≥10 6 CFU/ml have been proposed [30-33]. In addition, many laboratories continue to disregard s-QBC of <10 5 CFU/ml for Gram-positive bacterial uropathogens, and there remains debate regarding the prognostic value of s-QBC of <10 4 CFU/ml for diagnosis of UTI due to different organisms [34]. …”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of urine samples collected using specific techniques to avoid vaginal contaminants, from patients and healthy volunteers, has revealed a wide range of colonizing organisms that might be implicated in lower urinary tract dysfunction 48 . Evidence of exacerbation of lower urinary tract symptoms (LUTS) in association with both planktonic bacteria in the urine and urothelial colonization by bacteria has been reported [49][50][51] , but it remains unclear which species of bacteria may be responsible.…”
Section: Urgency Urinary Incontinencementioning
confidence: 99%
“…This diagnostic threshold is important given the association between low-CFU bacteriuria count (<1,000 CFU per ml), urinary incontinence 50 and refractory LUTS. In those with a history of recurrent UTIs, requesting the results of the previous microscopy, culture and antibiotic sensitivity analyses can assist in confirming the diagnosis, determining the correct treatment based on sensitivities and determining whether the UTIs are recurrent or persistent 1 .…”
Section: Urological Testsmentioning
confidence: 99%